Adherence to screening guidelines for gestational diabetes in pregnancy - Grönvall, Lina (UiT Norges arktiske universitet, 2020)
Background/Objective: There are major controversies in screening and diagnostic criteria for gestational diabetes. In 2017, new national guidelines were implemented in Norway. The aim of this study is to evaluate change in size of risk population for GDM, adherence to screening guidelines and follow up before and after implementation of the new guidelines. Method: This study is a retrospective case-series study. Data from women giving birth at the University Hospital of North Norway and the local maternity wards in Troms during first half-years of 2013 and 2018 was collected from the electronic medical record PARTUS and the antenatal fact sheet. Included were women giving birth after 29 weeks’ gestation, with singleton fetus and no pre-pregnancy DM (N=1349). Categorical variables were age (17-24, 25-34, 35-39 and 40 through highest), pre-pregnancy BMI (lowest thru 24.99, 25.00-26.99, 27.00 thru highest), parity (nulliparous/parous), ethnicity (high risk/low risk), follow up (neglected/lifestyle intervention/metformin/insulin), obstetric risk assessment (yes/no). Primary outcomes were change in size of risk population across guidelines, adherence to screening guidelines and prevalence of GDM. Statistical analyses were done using IBM SPSS with Chi-square test. P-values < 0.05 were considered statistically significant. Results: After changing the screening guidelines in 2017, the population at risk for GDM increased from 46.4% to 67.6% (p<0.01). However, only 28.7% in 2013 and 49.2% in 2018 were actually exposed to OGTT (p<0.01). Of those correctly screened 16.7% (15/90) of the women were diagnosed with GDM in 2013, respectively 10.7% (24/224) in 2018. Overall 2.2% (15/676) of the cohort was diagnosed with GDM in 2013 and 3.6% (24/673) in 2018. In 2018 41.7% of the women were diagnosed with GDM based on the fasting plasma glucose test solely. Among the women diagnosed with GDM, follow up was neglected in 13.3% in 2013, and in 20.8% in 2018. Of the remaining women, all women eligible for obstetric risk ...